Efficacy and safety evaluation of a novel hemostatic gelatin matrix for intraoperative hemostasis: a prospective, randomized controlled trial - Peng Luo; Qi Lai; Li Xu; Zhenzhong Chen; Runsheng Guo; Banglin Xie; Ping Yi; Zhiying Yang; Bin Zhang (Scientific Reports)
Abstract Borayflo Haemostatic matrix is a new absorbable hemostatic gelatin matrix which can be used for intraoperative assisted hemostasis. In a prospective, multicenter, non-inferiority, randomized controlled trial, a total of 354 subjects were recruited from the departments of hepatobiliary surgery, obstetrics and gynaecology and orthopaedics of 4 hospitals and randomly allocated to test group (Borayflo Haemostatic matrix) or control group (Surgiflo Haemostatic matrix) in a 1:1 ratio. In the modified intention-to-treat population, 163 (93.14%) of 175 subjects in the test group versus 167 (94.89%) of 176 subjects in the control group successfully achieved hemostasis within 5 min (P > 0.05). Non-inferiority for effective rates of hemostasis at 5 min to Surgiflo Haemostatic matrix was shown in the study (treatment difference: -1.74% [95%CI, -6.70–3.22%] for modified intention-to-treat population). In terms of efficacy and safety, the new hemostatic gelatin matrix (Borayflo Haemostatic matrix) is equivalent to Surgiflo Haemostatic matrix. There was no significant difference in the incidence of AEs or SAEs between the test and control groups(P > 0.05). In addition, Borayflo Haemostatic matrix is a domestically produced haemostatic gelatin product, an advantage that will reduce the cost of surgical haemostasis for Chinese patients.